Pengaruh Profitabilitas, Leverage, Komisaris Independen, Kepemilikan Institusional, dan Ukuran Perusahaan terhadap Tax Avoidance pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2020-2024 - Septian Faiz Witana; Purwantoro; Anna Sumaryati; Ira Septriana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The study aims to analyze the effect of profitability, leverage, independent commissioners, institutional ownership, and company size on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Employing a quantitative method with a purposive sampling technique, 248 secondary data points from annual reports were obtained and analyzed using multiple linear regression with SPSS 25. The results indicate that profitability has an effect on tax avoidance, whereas leverage, independent commissioners, institutional ownership, and company size have no effect. Simultaneously, all variables have an effect on tax avoidance.